Potensi Chlorella sp. Isolat Air Gambut Terhadap Optimasi Pertumbuhan dan Kelangsungan Hidup Benih Ikan Betok (Anabas testudineus) - Maryani, Maryani; Rosita, Rosita; Gunawan, Irawadi; Fikriansyah, Fikriansyah; Najamuddin, Anang; Tsuraya, Faridah; Wanto, Wahyu Anggar; Kalalinggi, Septaria Y (Jurnal Akuakultur Sungai dan Danau, 2026)
This study aims to evaluate the potential of peat water microalgae Chlorella sp. on the survival and growth of Betok fish (Anabas testudineus) fingerlings. An experimental method was employed using a Completely Randomized Design (CRD) consisting of three dosage treatments (A: 10 mL, B: 20 mL, C: 30 mL) with three replications. Parameters observed included Survival Rate (SR), absolute weight growth, absolute length growth, and Specific Growth Rate (SGR) over a 42-day rearing period. The results indicated that the administration of peat water microalgae had no significant effect ($P > 0.05$) on any of the tested parameters. However, visually, treatment C (30 mL) showed the highest results with a survival rate of 87.0%, absolute weight growth of 0.64 g, absolute length growth of 1.00 cm, and SGR of 1.13%. This suggests that nutrient intake from microalgae at the fingerling stage is predominantly used for maintaining physiological functions and suppressing environmental stress rather than somatic growth. Water quality parameters during the study remained within the optimal range, with temperatures of 26.0–27.5°C, pH 5.42–6.91, and DO 5.4–6.9 mg/L.